"Familiar Artifice": Ways of Telling in the Short Story, Psychoanalysis, and Alice Munro's "The Moons of Jupiter". (February 2022) - Rizq, Rosemary
Theoretical ideas about "narrative coherence" and "autobiographical competence" remain prevalent in contemporary therapeutic culture, and are frequently deployed in the service of the patient's producing a narrative "I" that can tell its own story. A preference for novelistic accounts of the self is countered here by proposing the short story form as an alternative model for the telling of a self within psychoanalysis. Alice Munro's "The Moons of Jupiter, " the roots of the short story form in fable, and a rereading of Freud's Totem and Taboo are used to illuminate how the short story may be seen as an exemplary tale paralleling the origin of the self in its identification with the other.